2015
DOI: 10.1016/j.febslet.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase PP1‐NIPP1 activates mesenchymal genes in HeLa cells

Abstract: a b s t r a c tThe deletion of the protein phosphatase-1 (PP1) regulator known as Nuclear Inhibitor of PP1 (NIPP1) is embryonic lethal during gastrulation, hinting at a key role of PP1-NIPP1 in lineage specification. Consistent with this notion we show here that a mild, stable overexpression of NIPP1 in HeLa cells caused a massive induction of genes of the mesenchymal lineage, in particular smooth/cardiac-muscle and matrix markers. This reprogramming was associated with the formation of actin-based stress fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…S1C). A very mild overexpression of NIPP1 in stable HeLa cell lines (<10%), due to promoter leakage from the non-induced transgenes, causes the expression of mesenchymal genes (Van Dessel et al, 2015). However, this low level of overexpression had no effect on the progression through mitosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1C). A very mild overexpression of NIPP1 in stable HeLa cell lines (<10%), due to promoter leakage from the non-induced transgenes, causes the expression of mesenchymal genes (Van Dessel et al, 2015). However, this low level of overexpression had no effect on the progression through mitosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hela Tet-off cell lines expressing Flag-tagged NIPP1 variants in the absence of doxycycline (Dox) and Flip-In T-REx cell lines expressing EGFP or EGFP-tagged NIPP1 variants in the presence of Dox were obtained as described previously (Tanuma et al, 2008;Van Dessel et al, 2015). Transfections were carried out using a commercial kit (Jet-Prime, Polyplus), according to the manufacturer's instructions.…”
Section: Cell Culture and Imagingmentioning
confidence: 99%
“…There are no data available regarding alterations in PP1 activity and/or substrate phosphorylation for the inducible and conditional NIPP1 KOs. However, various biochemical and cellular assays have revealed that known cellular NIPP1 functions (pre-mRNA splicing and transcription) are largely dependent on both association with PP1 and recruitment of substrates [38,110,114]. Mice that inducibly express the central part of NIPP1 (NIPP1 ) in the forebrain showed a decreased nuclear PP1 activity and increased histone H3 phosphorylation at serine 10 ( Table 3).…”
Section: Cellular-context Dependent Functions Of Nipp1mentioning
confidence: 99%
“…NIPP1 can silence transcription as it constitutes part of a protein silencing complex that includes the transcriptional repressor EED and histone deacetylase HDAC2 [39, 40]. NIPP1 can also activate transcription as it induces expression of mesenchymal genes in HeLa cells [41]. We recently reported that NIPP1 represses expression of neuregulin-1, a heparin-binding neurotrophic factor [42].…”
Section: Regulation Of Hiv-1 Transcription By Protein Phosphatase-1mentioning
confidence: 99%